Outcome of Patients Underwent Emergency Department Thoracotomy and Its Predictive Factors - Paydar, Shahram; Moghaninasab, Abdoshahid; Asiaei, Elham; Sabetian Fard Jahromi, Golnar; Bolandparvaz, Shahram; Abbasi, Hamidreza (Archives of Academic Emergency Medicine, 2014)
Introduction: Emergency department thoracotomy (EDT) may serve as the last survival chance for patients who arrive at hospital in extremis. It is considered as an effective tool for improvement of traumatic patients’ outcome. The present study was done with the goal of assessing the outcome of patients who underwent EDT and its predictive factors. Methods: In the present study, medical charts of 50 retrospective and 8 prospective cases underwent emergency department thoracotomy (EDT) were reviewed during November 2011 to June 2013. Comparisons between survived and died patients were performed by Mann-Whitney U test and the predictive factors of EDT outcome were measured using multivariate logistic regression analysis. P < 0.05 considered statistically significant. Results: Fifty eight cases of EDT were enrolled (86.2% male). The mean age of patients was 43.27±19.85 years with the range of 18-85. The mean time duration of CPR was recorded as 37.12±12.49 minutes. Eleven cases (19%) were alive to be transported to OR (defined as ED survived). The mean time of survival in ED survived patients was 223.5±450.8 hours. More than 24 hours survival rate (late survived) was 6.9% (4 cases). Only one case (1.7%) survived to discharge from hospital (mortality rate=98.3%). There were only a significant relation between ED survival and SBP, GCS, CPR duration, and chest trauma (p=0.04). The results demonstrated that initial SBP lower than 80 mmHg (OR=1.03, 95% CI: 1.001-1.05, p=0.04) and presence of chest trauma (OR=2.6, 95% CI: 1.75-3.16, p=0.02) were independent predictive factors of EDT mortality. Conclusion: The findings of the present study showed that the survival rate of trauma patients underwent EDT was 1.7%. In addition, it was defined that falling systolic blood pressure below 80 mmHg and blunt trauma of chest are independent factors that along with poor outcome.